Atypical Presentation of Herpes Simplex Virus 1 Encephalitis in Pediatric Age - Gulizia, Carmen; Smilari, Pierluigi; Greco, Filippo; Fontana, Alessandra; Ceccarelli, Manuela; Venanzi Rullo, Emmanuele; Nunnari, Giuseppe; Pavone, Piero (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The annual incidence of herpes simplex encephalitis (HSE) is 1:250–500 thousand in developed countries, which makes it the most common viral cause of encephalitis. Encephalitis caused by HSV-1 probably accounts for most of the cases in the Herpesviridae family and typically affects older children. CASE REPORT: An atypical presentation of pediatric herpetic encephalitis is reported. The child presented with recurrent seizures that were initially unresponsive to several anticonvulsant drugs. EEG and MRI of the brain were not effective for diagnosis. PCR analysis of the cerebrospinal fluid indicated positivity for HSV DNA and was crucial for the diagnosis as a highly sensitive and specific test. CONCLUSION: Based on the clinical presentation of the child, viral encephalitis was deemed to be the most likely aetiological condition.